2014
DOI: 10.2108/zs130179
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and Long-Distance Overseas Dispersals of Island Populations of the Ryukyu Five-Lined Skink, Plestiodon Marginatus (Scincidae: Squamata), in the Ryukyu Archipelago, Japan, as Revealed by Mitochondrial DNA Phylogeography

Abstract: We assessed the historical biogeography of the Ryukyu five-lined skink, Plestiodon marginatus, and related species (P. stimpsonii and P. elegans). Our specific aims were to reveal the origin, tim- ing, and route of the colonization to three volcanic islands in the northern Tokara Group of the northern Ryukyus: Kuchinoshima, Nakanoshima, and Suwanosejima. We conducted phylogenetic analyses and divergence time estimation using a partial sequence of the mitochondrial cytochrome b gene for P. marginatus collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…Similarly, divergence of the Kumejima population from populations of Okinawajima and adjacent islets is also estimated to have taken place in the same period (Node D in Fig. ), being well compatible to those for a few other taxa examined so far (scincid lizards, Kurita and Hikida ; natricine snakes, Kaito and Toda ). The divergences in this location are also considered to have resulted from vicariance by the same geohistorical movements.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, divergence of the Kumejima population from populations of Okinawajima and adjacent islets is also estimated to have taken place in the same period (Node D in Fig. ), being well compatible to those for a few other taxa examined so far (scincid lizards, Kurita and Hikida ; natricine snakes, Kaito and Toda ). The divergences in this location are also considered to have resulted from vicariance by the same geohistorical movements.…”
Section: Discussionsupporting
confidence: 80%
“…; crocodile newts, Honda et al. ; five‐lined skinks, Kurita and Hikida ), and the Japanese coral snake is also well concordant with this estimation (Node C in Fig. , Table ).…”
Section: Discussionsupporting
confidence: 68%
“…Several researchers suggested that the Kuroshio Current, a major ocean current that flows north‐eastward from Taiwan, has been a major factor influencing overseas dispersal of organisms from southern to northern islands (Kurita & Hikida, ). The current is thought to have driven long‐distance dispersals of small terrestrial animals over thousands of kilometres.…”
Section: Discussionmentioning
confidence: 95%
“…This northward "stepping-stone by island distance" model of colonization may have been facilitated by the regionally dominant surface Kuroshio current, which originates at the equator and flows northerly towards the Philippines, Taiwan-Luzon volcanic belt and Japanese islands. The Kuroshio current is thought to be a strong oceanic mechanism in shaping the distribution of tropical sea grasses (Kuo, Kanamoto, Iizumi, Aioi, & Mukai, 2006) and population genetic structures of skinks in the Ryukyu Archipelago (Kurita & Hikida, 2014). However, the stepping-stone model of colonization in the Taiwan-Luzon volcanic belt has never been rigorously tested using a molecular phylogeographical approach, with the exception of some phylogenetic studies of shrews (Esselstyn & Oliveros, 2010), birds (Oliveros & Moyle, 2010) and geckos (Siler, Oaks, Cobb, Ota, & Brown, 2014), which indicated a direction of colonization from either Northern Taiwan (shrews) and Batanes (birds) or Southern Luzon (geckos).…”
Section: Introductionmentioning
confidence: 99%